2018
DOI: 10.12988/ces.2018.83126
|View full text |Cite
|
Sign up to set email alerts
|

Traffic control in a smart intersection by an algorithm with social priorities

Abstract: This research deals with the case of a smart intersection, where several cars approach the intersection from various directions, and a smart traffic light must decide about the time intervals of RED and GREEN in each direction, based not only on the number of vehicles in each lane, but also on other factors such as the type of vehicles (e.g. emergency vehicles), and the social characteristics of the passengers (e.g. a handicapped person, a student who is late for an exam). Those factors will be gleaned from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Several studies employed a smart social junction (SSJ) algorithm where traffic light timings are adjusted based on both traffic load and societal preferences [19,20,39,53]. To facilitate the implementation of this algorithm, the concept of conflict side (CS) was introduced.…”
Section: Smart Social Junction With Social Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies employed a smart social junction (SSJ) algorithm where traffic light timings are adjusted based on both traffic load and societal preferences [19,20,39,53]. To facilitate the implementation of this algorithm, the concept of conflict side (CS) was introduced.…”
Section: Smart Social Junction With Social Preferencesmentioning
confidence: 99%
“…Barzilai et al [20] suggested incorporating an innovative preference system based on the social characteristics of the vehicle driver (e.g., a handicapped person) or on its travel purpose (e.g., A doctor traveling to an emergency surgery at a hospital). The concept involves adjusting traffic signals according to both traffic load and social priority.…”
Section: Introductionmentioning
confidence: 99%
“…A system agent at the same time bids benevolently at a level which guarantees a minimum service quality for those not willing to pay. A smart traffic light in [82] decides on the time intervals of red and green based on various factors, including the social characteristics of passengers. They introduce a social preference parameter to make traffic handling more just, and to reduce driver stress (e.g.…”
Section: G Intelligent Intersectionsmentioning
confidence: 99%
“…Previous studies (Barzilay et al, 2018a;Barzilay et al, 2018b;Fine et al, 2019;Barzilay et al, 2020) have expanded the concept of a smart junction by introducing a social preference and a benefit factor for junction traffic management, combined with traffic load. Social preference is based on the social characteristics of the vehicle passengers (e.g.…”
Section: Introductionmentioning
confidence: 99%